2022
DOI: 10.3390/jfb13040177
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Antibacterial Properties of Conventional and Two Premixed Root Canal Filling Materials in Primary Teeth

Abstract: In this study, some physicochemical and antibacterial properties of three root canal filling materials for primary teeth, Calplus “CP” (Prevest DenPro, Lewes, DE, USA), Bio-C Pulpecto “Bio-CP” (Angelus, Basil, Londrina, Paraná, Brazil), and Zinc Oxide and Eugenol “ZOE” (Prevest DenPro, Lewes, DE, USA) were compared. For each material, the pH, solubility, contact angle, and crystalline microstructure under SEM were evaluated. Their antibacterial activity against Enterococcus faecalis was determined through dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
(49 reference statements)
1
19
0
Order By: Relevance
“…A pH-meter (CyberScan pH 510, Thermo Scientific, Waltham, Massachusetts, USA), was used to measure the pH of media (n = 5) at 3, 24 and 72 h. The calibration of pH-meter was performed using standard solutions at pH 10, 4 and 7 (Hanna Instruments, Lingolsheim, France). Distilled water was used to rinse and eliminate the previous solution from the pH electrode [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A pH-meter (CyberScan pH 510, Thermo Scientific, Waltham, Massachusetts, USA), was used to measure the pH of media (n = 5) at 3, 24 and 72 h. The calibration of pH-meter was performed using standard solutions at pH 10, 4 and 7 (Hanna Instruments, Lingolsheim, France). Distilled water was used to rinse and eliminate the previous solution from the pH electrode [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Currently, calcium silicate materials are used frequently in endodontic practice due to their great biological, mechanical, and physicochemical properties [ 35 , 36 ]. Ceraseal sealer, which was used in the present study, is one of these calcium silicate endodontic products that has demonstrated an alkaline pH and release of Ca 2+ ions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ceraseal sealer, which was used in the present study, is one of these calcium silicate endodontic products that has demonstrated an alkaline pH and release of Ca 2+ ions [ 23 ]. Therefore, these properties might enhance and provide for the mineralization process and the formation of hydroxyapatite tags in the dentinal tubules [ 21 , 23 , 29 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 10 s, the 5 µL drop was totally absorbed by the surface of BR which had the higher roughness values compared to BD and WR ( p < 0.05). Whatever the considered wetting model (Wenzel or Cassie–Baxter) [ 48 ], the higher roughness and hydrophilic surface would increase the adhesion, protein adsorption and the cellular attachment, and provide a superior biocompatibility [ 48 , 49 , 50 ]. In contrast, a decrease in cell proliferation and growth could be related to a critical roughness ration, where the elastic energy of the cell hinders the insertion of the cells into surface trenches, where cells install over the tips of the rough surfaces leading to only point-contact, which minimizes cell–surface interaction [ 51 ].…”
Section: Discussionmentioning
confidence: 99%